Efektivitas Bimbingan Kelompok Melalui Teknik Sosiodrama Dalam Meningkatkan Sikap Respek - Ida Mawarni Mendrofa; Hosianna Rodearni Damanik; Elizama Zebua; Mondang Munthe (Conseils : Jurnal Bimbingan dan Konseling Islam, 2024)
Students' respect for teachers and peers can be increased with sociodrama technique group guidance services. The aim of this research is to reveal how effective sociodrama technical group guidance services are in increasing students' respect for teachers and peers. This study uses a quantitative approach with a quasi-experimental design and an experiment with a one group pretest-posttest design. Data was collected using a questionnaire and analyzed quantitatively and the results were described. The research location is SMP Negeri 2 Gunungsitoli Utara. The research population was all 69 class VII students and the sample was drawn by purposive sampling, 48 people for the experiment and one class for the control class. The research results concluded that sociodrama technique group guidance services were effective in increasing students' respectful attitudes and lecture or conventional methods were not effective in increasing students' respectful attitudes. This is proven by the very high increase in their respect. The students' respectful attitude before being given treatment, namely sociodrama technical group guidance services to 48 people with a test average of only 69.67%, was in the ineffective category. Meanwhile, after being given treatment, namely the sociodrama technical group guidance service and the average post-test result was 97.67 with the category being effective and the treatment result was 28%. It is recommended that guidance and counseling teachers or school counselors plan and implement sociodrama technique group guidance services with appropriate material to increase students' respect.